IMPLEMENTATION OF ITE LAW INFORMATION POLICY IN THE DIGITAL AGE - Shindi Rizky Putri; Abdul Karim Batubara (Jurnal Kebijakan Publik, 2026)
Social media provides a space for freedom of expression, but on the other hand, it also gives rise to various problems such as the spread of hoaxes, hate speech, defamation, bullying, and privacy violations. This study aims to analyze the implementation of information policies based on the Electronic Information and Transactions Law (ITE Law) in handling the spread of content on TikTok, as well as evaluate the effectiveness of sanctions for violations. This study uses a qualitative approach with observation, documentation, and content analysis methods for several cases that went viral on TikTok, such as insulting the teaching profession (@riezky.kabah), blasphemy (@galihloss3), and assault and the spread of immoral content (@qila). The data analysis technique uses the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The implementation process takes place through the stages of violation detection, early intervention (takedown), law enforcement, and evaluation and application of sanctions. The research findings indicate that law enforcement has been carried out procedurally, but its effectiveness is still partial. The deterrent effect has not been fully formed, especially in cases of digital recidivism. Furthermore, there is a gap between regulations and the level of digital literacy of the community. Therefore, the implementation of information policy needs to transform from a reactive-punitive approach to a collaborative and preventative approach based on digital literacy. Libraries, as information management institutions, have a strategic role in strengthening information literacy to create a healthy, responsible, and equitable digital ecosystem.